10-year results of ReCap hip resurfacing arthroplasty: a non-designer case series. Issue 4 (July 2019) - Kiran, Manish; Santhapuri, Sunil; Moeen, Sara; Merchant, Irfan; Arvinte, Dan; Sood, Manoj
Introduction: We present the 10-year results of the ReCap Magnum HRA system in a consecutive single surgeon's series from a non-designer centre. Patients and methods: Hip resurfacing arthroplasty (HRA) was performed in active males under 65 years and in pre-menopausal females with adequate bone density proven by a DEXA scan. Clinical follow-up; annual Oxford hip scoring, UCLA scoring and whole blood metal ion level measurement. Kaplan-Meier method was used to determine survivorship with revision as the end point. Radiographs were analysed for; acetabular inclination, notching, neck thinning and change in implant position. 72 HRAs were performed in 66 patients with a mean age of 45.7 years. The mean follow-up was 10.63 ± 0.54 years (range 10–11.75 years). Results: The survivorship of the cohort at minimum 10 years was 97.22% (95% confidence interval 94.14–99.01). There was a significant improvement in the Oxford Hip Score from 15.77 ± 4.33 to 45.67 ± 4.43 ( p < 0.001) and the UCLA score from 3.14 ± 0.74 to 7.07 ± 1.16 ( p < 0.001). Mean whole blood cobalt and chromium levels were 28.83 ± 8.42 nmol/l and 39.93 ± 9.64 nmol/l respectively. There were 2 revisions, due to avascular necrosis and implant failure. In our series the implant has performed well with <1% failure per year. We did not note any difference between the genders, since all the females in our series had been screened for osteopenia using a DEXA scan. All our patients returned to an active lifestyle which was maintained at final follow-up. Conclusion: Strict selection criteria and a well-designed implant result in good long-term functional and radiological results with hip resurfacing.